Abnormal neural response to phonological working memory demands in persistent developmental stuttering. Issue 1 (26th August 2018) - Yang, Yang; Jia, Fanlu; Fox, Peter T.; Siok, Wai Ting; Tan, Li Hai
Abstract : Persistent developmental stuttering is a neurological disorder that commonly manifests as a motor problem. Cognitive theories, however, hold that poorly developed cognitive skills are the origins of stuttering. Working memory (WM), a multicomponent cognitive system that mediates information maintenance and manipulation, is known to play an important role in speech production, leading us to postulate that the neurophysiological mechanisms underlying stuttering may be associated with a WM deficit. Using functional magnetic resonance imaging, we aimed to elucidate brain mechanisms in a phonological WM task in adults who stutter and controls. A right‐lateralized compensatory mechanism for a deficit in the rehearsal process and neural disconnections associated with the central executive dysfunction were found. Furthermore, the neural abnormalities underlying the phonological WM were independent of memory load. This study demonstrates for the first time the atypical neural responses to phonological WM in PWS, shedding new light on the underlying cause of stuttering.